Share Price of Bank BTPN Syariah: The Role of Return on Equity and Return on Assets - Vemy Suci Asih; Wisnu Uriawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research was motivated by the high interest of investors in PT BTPN Syariah Tbk shares which caused the value of the stock price to increase progressively even though it was hit by the economic crisis due to the COVID-19 pandemic. This study aims to analyze and find out how much influence return on equity (ROE) and return on assets (ROA) have on the stock price of PT BTPN Syariah Tbk in the Indonesian Islamic capital market. The research method used is descriptive verification method with a quantitative approach. Researchers used secondary data obtained from the official website of PT BTPN Syariah Tbk (www.btpnsyariah.com). The analysis technique in this research is descriptive statistical analysis, classical assumption test, multiple linear regression, hypothesis testing using t test (partial) and F test (simultaneous), and coefficient of determination test. The results showed that partially, the t-test of the ROE variable did not have a positive effect on stock prices. While the ROA variable has a positive influence on stock prices. Furthermore, based on simultaneous hypothesis testing (F test), the results obtained that the ROE and ROA variables have a positive and significant effect on stock prices. In addition to testing the coefficient of determination, the variation of the stock price variable (Y) can be explained by the variation of the independent variable, namely ROE and ROA as much as 45.5%. While the remaining percentage of 54.5% was explained in other variables outside of this study.